The constitutional status and educational development of the non-Albanian and Albanian minoritie in Yugoslavia 1945-1974 - BASHA, Kosovar (Historia i Świat, 2023)
The paper carefully deals with the constitutional aspect and the development of education in Yugoslavia, which in the general background affects the general minorities in Yugoslavia such as Bulgarians, Italians, Germans, Hungarians and with special emphasis – Albanians. The author has followed the descriptive and analytical scientific methods for dealing with this important issue for general historiography. A serious Yugoslav and Albanian literature covering this socially and scientifically important study has been used.